2011
DOI: 10.1080/01639625.2010.538361
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Informal Social Control Against the Highly Stigmatized

Abstract: Both formal and informal social controls are powerful guides and restrictions on behaviors. This study assesses the types of informal social control-observations and interventions, and proposes a division of intervention strategies into two subforms-expressions of disapproval and direct sanctions. Using data from two states (Kansas and Oklahoma) analyses show that registered sex offenders are subject to a wide variety of informal community social control efforts. These offenders feel moderate to high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Some scholars (Tewksbury and Lees 2006;Robbers 2009) have shown that registered sex offenders do experience negatively interpreted direct interactions with others, which often function to limit individuals' social engagement (Robbers 2009). Others have also demonstrated that registered sex offenders experience enhanced levels of informal social control in the forms of public recognition, expressions of disapproval from others and direct sanctioning actions that are all associated with increased levels of stress (Mustaine and Tewksbury 2011). However, what to date has been missing from our understandings of these experiences is the way in which such actions and reactions are emotionally and psychologically experienced.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some scholars (Tewksbury and Lees 2006;Robbers 2009) have shown that registered sex offenders do experience negatively interpreted direct interactions with others, which often function to limit individuals' social engagement (Robbers 2009). Others have also demonstrated that registered sex offenders experience enhanced levels of informal social control in the forms of public recognition, expressions of disapproval from others and direct sanctioning actions that are all associated with increased levels of stress (Mustaine and Tewksbury 2011). However, what to date has been missing from our understandings of these experiences is the way in which such actions and reactions are emotionally and psychologically experienced.…”
Section: Discussionmentioning
confidence: 96%
“…Beyond the formal labeling and sanctioning that is criminal conviction, registration and community notification, so too do registered sex offenders commonly experience informal social control in the community (Mustaine and Tewksbury 2011). Self-reports from registered sex offenders reveal three types of informal social control that are typically experienced: recognized observation, expressions of disapproval from others, and direct sanctioning actions (Mustaine and Tewksbury 2011). And, not only are such community efforts recognized and experienced, but so too are they associated with increased levels of stress.…”
Section: Social Responses To Sex Offendersmentioning
confidence: 99%
“…"Normals" (or the public, assuming that they are without a sexual conviction history) hold a greater negative attitude toward RSOs than ex-offenders without sexual convictions (Rade et al, 2016). Correspondently, RSOs have reported feelings of inferiority and ostracism when among the general populace (Burchfield & Mingus, 2008;Evans & Cubellis, 2015;Levenson & Cotter, 2005;Levenson, D'Amora, & Hern, 2007b;Mustaine & Tewksbury, 2011a; see Tewksbury, 2012;Tewksbury & Lees, 2006;Zevitz & Farkas, 2000b). Feelings of contempt against RSOs by the public parallel with Goffman's (1963) thesis of the reactions expressed by "normals" to the presence of stigmatized persons.…”
mentioning
confidence: 62%
“…Pope, 2008;Wentland et al, 2014). The public's concerns may also contribute mixed results are greater regarding the stigma associated with the label of being a sex offender rather than their classification category (Mustaine & Tewksbury, 2011a). In support, high-risk RSOs (as determined by a risk-assessment instrument) did not encourage a greater adoption of self-protective behaviors by community members, which lent credence that the public does not differentiate RSOs by their status (Bandy, 2011).…”
Section: Sex Offendersmentioning
confidence: 72%
See 1 more Smart Citation